An exploration of the connotation of clinical dental radiology education for medical radiation students in Taiwan in 2022 - Cheng, Feng-Chou; Chen, Mu-Hsiung; Chen, Meng-Chi; Wan, Yu-Wen; Hsu, Pei-Yu; Wang, Yin-Lin; Chiang, Chun-Pin (Journal of dental sciences, 2023)
In Taiwan, the dental radiology has a history of more than 100 years. However, medical radiation schools or teaching hospitals have not yet established a set of standard learning content for dental radiology internship. We used the observational method and dental radiology teaching survey to explore the connotation of clinical dental radiology education for medical radiation students in Taiwan. There were 64 dental departments of hospitals with their own independent dental radiology departments in Taiwan in 2022. Among them, 58 (90.63%) were in the teaching hospitals. Of the 58 dental radiology departments in the teaching hospitals, 40 (68.97%) had medical radiation interns in their dental radiology departments. There was a complete set of seven training items for dental radiology internship. The mean training items in the medical centers (4.94) was significantly higher than that in the regional hospital (3.9) (P < 0.05). No matter what level of hospital, it is the most common way to implement the training mode with preclinical exercises and then clinical practice. In Taiwan, the current status of dental radiology teachers in the teaching hospital is indeed seriously insufficient. It is necessary to establish a standard dental radiology education system, including setting one common dental radiology subject for medical radiation students, and the relevant regulations to formulate the basic requirements of the training items and training hours for dental radiology internship. Thus, medical radiation interns can acquire the operation skills related to dental X-ray machines after completing the internship training.